Thermal pollution in rivers due to cooling water from power plants and implications for system resilience to future change - Du, Tianyang (2024)
Thermal effluents discharged from power plant cooling systems can cause abrupt changes in water temperature and impose substantial thermal stress on aquatic organisms. Substantial efforts have been made to alleviate thermal stress by improving legal regulations and treating effluent using new technologies such as combined cycle gas turbine and recirculating cooling. However, riverine thermal pollution from cooling systems remains a concern due to rapid and continued expansion of thermal power plants globally. In addition, the impact of thermal effluents on rivers has been poorly studied because of limited data availability and accuracy. This thesis aimed to evaluate the impact of thermal pollution from power plants on rivers and aquatic life across different spatial and temporal scales. Given that critical resources such as labour, material and finance are limited, it is important to locate and evaluate power plants that generate large amounts of thermal pollution, to prioritise the implementation of new technologies and regulations to reduce impacts. Therefore, a computationally simple and low data-intensive index was developed as a tool for identifying ‘hotspots’ that need particular attention. The effectiveness of the index was validated by the success in assessing and locating the power plants that potentially generate a large amount of thermal pollution. Follow-up scenario-based analyses were also performed to show that the index, in combination with background information can provide accurate assessments of thermal pollution and be not confined to the plants using once-through cooling systems. Although the new index makes it possible to assess the impact of power plant effluent and identify rivers that are particularly vulnerable to effluent release, the interaction and cumulative impact of multiple power plants on the same river, or in the same catchment, have not been examined. We thus investigated this source of thermal pollution by simulating hypothetical power plant discharge scenarios in a conceptual water temperature model at the whole-river scale. The results indicated that the effluent discharge made a greater contribution to temperature increase than the effluent temperature, and the remaining energy advected from the effluent of upstream power plant was combined with the heat input from the downstream power plant to cause cumulative thermal impacts. The arrangement of power plants along a river played an important role in alleviating the cumulative impacts. It was also found that water temperature change resulting from power plant discharge could be further complicated by the operation mode and climate change. Aquatic ectotherms are dependent on the temperature of surrounding water and can be greatly influenced by elevated water temperatures due to thermal discharges and climate change. Therefore, these organisms have to make necessary physiological and behavioural adjustments (i.e. acclimation) to protect themselves from the negative consequences of elevated temperatures. However, the tolerance and survival of individuals at stressful temperatures can differ markedly, partly determined by the thermal history (i.e. habitat temperature regime) experienced by the animal. Hence, we investigated the response of aquatic ectotherms with different thermal histories to acute and chronic thermal stress via laboratory experiments with steady and variable temperatures. Organisms from thermally contrasting sites were both vulnerable to a persistently high temperature. The continuous expression of HSPs which reallocates energy from important processes like growth and respiration, possibly deteriorating animal health and increasing the difficulty in survival. When exposed to intermittently high temperatures, organisms inhabiting thermally more variable site were more tolerant to acute thermal stress than those inhabiting thermally less variable site. The improved thermal tolerance can be attributed to the wider thermal range and greater thermal variability of their habitat. By examining the impact and distribution of power plant thermal pollution, this research revealed the crucial role of thermal power plants in altering thermal regimes of streams and rivers worldwide.